Impact of Online Education on Student Learning during the Pandemic - Hermeet Kohli; Donna Wampole; Amarpreet Kohli (Studies in Learning and Teaching, 2021)
Using qualitative exploratory research, we documented the experiences of 90 undergraduate and graduate students on how online education was affecting their learning during the pandemic. Data was collected from School of Social Work students at a northeastern public university in the United States. The participants were unsatisfied with the unexpected disruption to online education. However, they had adjusted to digital learning, and stated that they would rather have subpar education than put self and others in danger due to COVID-19. The major challenges that the students encountered are: (a) struggle with online education, (b) difficulty connecting with instructors, (c) lack of motivation, (d) losses, (e) difficulty accessing other learning resources, and (f) unsafe/inaccessible home environment. Recommendations are provided for instructors and administrators to support students in these challenging times.